Community Satisfaction Of Recipients Of Social Assistance For The Family Hope Program In Depok Sub-District - Kharunnisa Nazifah, Hilda; Nurjannatiya, Maudy; Hidayat, Moh. Taufik; Heryanto, Yanto (Pelopor Publikasi Akademika, 2024)
This study was conducted to find out the extent of community satisfaction with the recipients of social assistance of the Family Hope Program in Depok District, Cirebon Regency. Depok District is the location of the research and the community receiving social assistance from the Family Hope Program is the subject of this research. This study uses a quantitative method with a descriptive design. The data was collected through the distribution of questionnaires to the community in Depok District which became a research sample from 12 existing villages. This study uses 7 assessment indicators to measure community satisfaction. Among them, satisfaction with the assistance provided, satisfaction with the assistance received as expected or not, satisfaction with the attitude of officers in the disbursement process, satisfaction with the government in paying attention to the needs and desires of the community, satisfaction with the government in responding to problems that occur, satisfaction with the overall performance of officers in the disbursement of assistance, and satisfaction with the suitability of the promised assistance with the assistance that Retrieved. There are 2 indicators that are still complained about by the community, such as satisfaction with the government in responding to the problems that occur, and the suitability of the promised assistance with the assistance obtained. According to this study, one of the factors for these problems is the lack of communication and clarity of information between the Government (Cirebon Regency Social Service) and PKH assistants and the recipient community.